MAPK10 Expression as a Prognostic Marker of the Immunosuppressive Tumor Microenvironment in Human Hepatocellular Carcinoma - Li, Huahui; Li, Yuting; Zhang, Ying; Tan, Binbin; Huang, Tuxiong; Xiong, Jixian; Tan, Xiangyu; Ermolaeva, Maria A.; Fu, Li (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) remains a devastating malignancy worldwide due to lack of effective therapy. The immune-rich contexture of HCC tumor microenvironment (TME) makes this tumor an appealing target for immune-based therapies; however, the immunosuppressive TME is still a major challenge for more efficient immunotherapy in HCC. Using bioinformatics analysis based on the TCGA database, here we found that MAPK10 is frequently downregulated in HCC tumors and significantly correlates with poor survival of HCC patients. HCC patients with low MAPK10 expression have lower expression scores of tumor infiltration lymphocytes (TILs) and stromal cells in the TME and increased scores of tumor cells than those with high MAPK10 expression. Further transcriptomic analyses revealed that the immune activity in the TME of HCC was markedly reduced in the low-MAPK10 group of HCC patients compared to the high-MAPK10 group. Additionally, we identified 495 differentially expressed immune-associated genes (DIGs), with 482 genes downregulated and 13 genes upregulated in parallel with the decrease of MAPK10 expression. GO enrichment and KEGG pathway analyses indicated that the biological functions of these DIGs included in cell chemotaxis, leukocyte migration and positive regulation of the response to cytokine-cytokine receptor interaction, T cell receptor activation and MAPK signaling pathway. Protein-protein interaction (PPI) analyses of the 495 DIGs revealed 5 potential downstream hub genes of MAPK10, including SYK, CBL, VAV1, LCK and CD3G. Several hub genes such as SYK, LCK and VAV1 could respond to the immunological costimulatory signaling mediated by the transmembrane protein ICAM1, which was identified as a downregulated DIG associated with low-MAPK10 expression. Moreover, ectopic overexpression or knock-down of MAPK10 could upregulate or down-regulate ICAM1 expression via phosphorylation of c-jun at Ser63 in HCC cell lines, respectively. Collectively, our results demonstrated that MAPK10 downregulation contributes to the immunosuppressive TME of HCC and this gene might serve as a potential immunotherapeutic target and a prognostic factor for HCC patients.